Structural Reforms and External Rebalancing - Culiuc, Alexander (IMF Working Papers; Working Paper ;, 2017)
Empirical research on structural reforms has focused primarily on their impact on growth and productivity. Yet an often-invoked rationale for structural reforms is their impact on external adjustment. This paper finds little evidence that structural reforms improve the current account in the short run, but they can increase the responsiveness and resilience of the economy to external shocks. In particular, elasticities of exports with respect to the real effective exchange rate increase with some structural indicators, suggesting that structural reforms facilitate the reallocation of resources to the tradable sector in response to a negative external shock. The paper concludes that structural reforms, while not having an immediate positive impact on the current account balance, can be an important complement to traditional macroeconomic adjustment.